Evaluación de la formulación para una suela de caucho traslúcido a partir de la vulcanización con peróxidos orgánicos para la empresa Croydon Colombia S.A. (2018)
This project evaluates the formulation of a translucent rubber compound for sole using natural and synthetic rubber, for the company Croydon Colombia S.A., from the vulcanization with organic peroxides, which allows to eliminate accelerators and other additives that stain, allowing to obtain the desired appearance of the compound. Initially 9 mixtures of natural and synthetic rubber were made, varying the proportions of each, but it was observed that natural rubber affects the color of the compound, so it was eliminated; 24 more mixtures are proposed, which do not include natural rubber. Because all the mixtures that do not contain natural rubber were translucent, it was not possible to give a complete answer to the first objective of determining the adequate proportions of synthetic and natural rubber, so, it was solved simultaneously with the second objective, finding the base formulation.